Edukasi Literasi Hukum dan Bahaya Fatalitas Berkendara Untuk Menurunkan Intensi Balap Liar Pada Remaja di Porong Sidoarjo - Yusril Pratama Hidayat (Jurnal Pengabdian Masyarakat (Bisma), 2026)
The phenomenon of illegal street racing in the Sidoarjo region, particularly along the Porong Arterial Road, is a serious social problem predominantly involving teenagers and posing a high risk of fatal accidents. This community service initiative aims to provide comprehensive education to raise legal awareness and promote safe driving practices among teenagers in Porong, thereby reducing participation in illegal street racing. The method used in this community service project is a qualitative descriptive approach that applies the Asset-Based Community Development (ABCD) framework, which utilizes human, social, and physical assets within the local community. The results of the activity indicate an increase in participants' legal literacy regarding the penalties under Law No. 22 of 2009, as well as a decrease in the intensity of intentions to engage in illegal street racing, based on post-activity questionnaire results. Through legal literacy interventions and visualizations of fatalities, participants began to recognize the real risks of accidents, ultimately contributing to a safer community.